Organometallic Half-Sandwich Iridium Anticancer Complexes - Liu, Zhe; Habtemariam, Abraha; Pizarro, Ana M; Fletcher, Sally A; Kisova, Anna; Vrana, Oldrich; Salassa, Luca; Bruijnincx, Pieter C. A; Clarkson, Guy J; Brabec, Viktor; Sadler, Peter J (Journal of medicinal chemistry, 2011)
The low-spin 5d6 IrIII organometallic half-sandwich complexes [(η5-Cpx)Ir(XY)Cl]0/+, Cpx = Cp*, tetramethyl(phenyl)cyclopentadienyl (Cpxph), or tetramethyl(biphenyl)cyclopentadienyl (Cpxbiph), XY = 1,10-phenanthroline (4−6), 2,2′-bipyridine (7−9), ethylenediamine (10 and 11), or picolinate (12−14), hydrolyze rapidly. Complexes with N,N-chelating ligands readily form adducts with 9-ethylguanine but not 9-ethyladenine; picolinate complexes bind to both purines. Cytotoxic potency toward A2780 human ovarian cancer cells increases with phenyl substitution on Cp*: Cpxbiph > Cpxph > Cp*; Cpxbiph complexes 6 and 9 have submicromolar activity. Guanine residues are preferential binding sites for 4−6 on plasmid DNA. Hydrophobicity (log P), cell and nucleus accumulation of Ir correlate with cytotoxicity, 6 > 5 > 4; they distribute similarly within cells. The ability to displace DNA intercalator ethidium bromide from DNA correlates with cytotoxicity and viscosity of Ir−DNA adducts. The hydrophobicity and intercalative ability of Cpxph and Cpxbiph make a major contribution to the anticancer potency of their IrIII complexes.